(untitled) (International Journal of Clinical Research, 2022)
Despite formidable advances throughout surgical disciplines spanning decades, plastic surgeons, especially microsurgeons, have most certainly ignored the memo to sufficiently recognize the alarming prevalence of musculoskeletal disorders (MSDs), a consequence of anti-ergonomic postures assumed during intricate procedures (eg. microsurgery), capable of physical limitations which can lead to early retirement. Collective ignorance of the aforementioned predicament is reflected in the plastic surgery literature wherein epidemiologically rigorous studies remain non-existent. Anecdotal reports evidencing the crippling effect of anti-ergonomic postures along with rigorous operative practices in plastic surgery procedures that have exaggerated operative durations suggest increased predisposition to occupational disorders like cervical disk disease, distal interphalangeal arthrosis, ligamentous injury, pulmonary embolism secondary to deep vein thrombosis and tendinitis. Remarkably, evidence in the literature highlights the commencement of musculoskeletal discomfort as early as in residency, even though previous studies have documented 35.4 years as the initiation point of musculoskeletal symptoms.